ATR–FTIR spectroscopy reveals involvement of lipids and proteins of intact pea pollen grains to heat stress tolerance - Lahlali, Rachid; Jiang, Yunfei; Kumar, Saroj; Karunakaran, Chithra; Liu, Xia; Borondics, Ferenc; Hallin, Emil; Bueckert, Rosalind (Frontiers in Plant Science, 2014)
With climate change, pea will be more frequently subjected to heat stress in semi-arid regions like Saskatchewan during flowering. The pollen germination percentage of two pea cultivars was reduced by heat stress (36°C) with an important decrease in cultivar ‘CDC Golden’ compared to ‘CDC Sage.’ Lipids, protein and other pollen coat compositions of whole intact pollen grains of both pea cultivars were investigated using mid infrared (mid-IR) attenuated total reflectance (ATR)–Fourier transform infrared (FTIR) spectroscopy. Curve fitting of ATR absorbance spectra in the protein region enabled estimation and comparison of different protein secondary structures between the two cultivars. CDC Sage had relatively greater amounts of α-helical structures (48.6–43.6%; band at 1654 cm-1) and smaller amounts of β-sheets (41.3–46%) than CDC Golden. The CDC Golden had higher amounts of β-sheets (46.3–51.7%) compared to α-helical structures (35.3–36.2%). Further, heat stress resulted in prominent changes in the symmetrical and asymmetrical CH2 bands from lipid acyl chain, ester carbonyl band, and carbohydrate region. The intensity of asymmetric and symmetric CH2 vibration of heat stressed CDC Golden was reduced considerably in comparison to the control and the decrease was higher compared to CDC Sage. In addition, CDC Golden showed an increase in intensity at the oxidative band of 3015 cm-1. These results reveal that the whole pollen grains of both pea cultivars responded differently to heat stress. The tolerance of CDC Sage to heat stress (expressed as pollen germination percentage) may be due to its protein richness with α-helical structures which would protect against the destructive effects of dehydration due to heat stress. The low pollen germination percentage of CDC Golden after heat stress may be also due to its sensitivity to lipid changes due to heat stress.